Comparison of DNA analysis, targeted metabolite profiling, and non-targeted NMR fingerprinting for differentiating cultivars of processed olives. (August 2020) - Crawford, Lauren M.; Janovick, Jennifer L.; Carrasquilla-Garcia, Noelia; Hatzakis, Emmanuel; Wang, Selina C.
Abstract: Genetic and metabolite analyses have been frequently employed in food traceability studies, although their effectiveness in heavily-processed products such as canned olives is uncertain. A robust method for identifying cultivars of processed table olives is necessary to ensure product authenticity and economic fairness. This study compared microsatellite analysis, fatty acid profiling, phenolic profiling, and NMR fingerprinting for differentiating cultivars of California-style olives. Methods were tested on domestic Manzanilla, domestic Sevillano, imported Hojiblanca, and imported Gordal olives. Microsatellites were successfully amplified in all cultivars except Hojiblanca, and Sevillano/Gordal were found to be genetically-related, possibly synonyms for the same genetic cultivar. Coupled with multivariate statistics, fatty acid profiling differentiated the three genetically-distinct cultivars, and NMR fingerprinting differentiated all four cultivars. Phenolic profile showed too much variability for effective discrimination. Future work includes expanding current models by size, cultivars, and type of table olive. Editor highlights: We compared genetic and metabolite analyses for differentiating cultivars of processed olives. Two cultivars were identical for all SSRs tested and are possibly synonyms for the same cultivar. Fatty acid-profiling robustly differentiated genetically-distinct cultivars. Phenolic profiling was not a reliable method for differentiation due to processing effects. Untargeted NMR fingerprinting effectively differentiated all cultivars.